PENCIPTAAN MAHKOTA TAAJMIRATMAA SEBAGAI REPRESENTASI VISUAL KEKAYAAN ALAM KUWAIT - Aqilla Yumna Ilma Izzati; Mutimmatul Faidah; Dewi Lutfiati; Biyan Yesi Wilujeng (Jurnal Tata Rias, 2025)
This research aims to describe the design concept, creation process, and evaluation results of the "Taajmiratmaa" crown as a visual representation of Kuwait's natural wealth and culture. The crown's design concept is inspired by the Arfaj flower, Kuwait's national flora symbolizing desert resilience and beauty, and Failaka Beach with its clear blue sea, representing peace and purity. Dominant colors of sea blue, white, and silver were chosen to reflect spirituality and elegance. The crown's form integrates Arfaj floral motifs with Islamic geometric elements, creating a graceful, feminine, yet strong impression. The primary material used is eva foam due to its lightweight and flexible properties, adorned with imitation Swarovski crystals in blue and white for a luxurious feel, resembling the sparkle of boron diamonds. The creation process began with developing a mood board and two alternative designs. Based on initial evaluations by three expert informants, Design 2 was selected for its superior aesthetics, proportion, and symbolism. The realization phase involved measuring the model's head, pattern making, material planning, main and detailed pattern drawing, Swarovski application in Arfaj flower motifs, bonsai wire foundation installation, and finishing with glitter application. The final evaluation of the realized crown was conducted by 30 respondents (makeup artistry students) using a Likert scale. The results showed an overall average score of 45 out of 50 points, with most respondents giving scores between 42-50 points. The most prominent aspects receiving high ratings were cultural theme suitability, color combination, and overall visual aesthetics. This indicates that the "Taajmiratmaa" crown successfully integrates Kuwaiti cultural elements with modern design, receiving high appreciation in both artistic and technical aspects. Keywords: Taajmiratmaa Crown, Kuwait's Natural Wealth, Arfaj Flower, Failaka Beach, Swarovski.